Representation of Justice in the Phenomenon of No Viral No Justice and the Shadow of the Electronic Information and Transaction Law - Muhamad Iqbal; Iin Indriani; Susanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The concept of viral has become a new phenomenon in society, which is different from oral rumors or traditional issues because it manifests itself in the form of content on social media. Although it is considered a channel for free speech, virality is often based on emotion and subjectivity, thus giving rise to debates regarding the justice it produces. The phenomenon of "No Viral No Justice" shows that public opinion is often used as the basis for social justice, which is dangerous because viral justice does not always reflect objective truth. On the other hand, the Information and Electronic Transactions Law (ITE Law) is actually designed to regulate the proportionate delivery of information, not to restrict freedom of opinion. However, the implementation of the ITE Law is often misinterpreted as a tool to suppress public voices, thereby creating a fear of speaking out. Therefore, it is important to understand that virality can be a tool to raise awareness of certain issues, but it should not be used as a means of public justice. In the framework of democracy, a balance between freedom of speech and information regulation is needed so that justice is maintained without sacrificing public discussion space.